Effect of Labour Bank-Karshika Karma Sena on the Livelihood of Agricultural Labour Households in Kerala - Aryakrishnan J U; Kingsly Immanuelraj; Renjini V R; Ranjit Kumar Paul; Sitaram Bishnoi; Shiv Kumar (Indian Journal of Extension Education, 2025)
Labour Bank-Karshika Karma Sena is an institutional intervention designed to address labour scarcity in the agricultural sector of Kerala. The study was conducted in two districts, viz Palakkad and Thrissur, based on the maximum paddy area and production. The total sample size was 176 agricultural labourers, entailing 80 participants and 96 non-participants pertaining to the year 2024. Agricultural labour work was the major contributor to employment for sample respondents. It was 71.12 per cent and 51.44 % for participants and non-participants, respectively. Income from agricultural labour activities formed a sizeable share in overall household income for participants, of which around 70% of the agricultural labour income was obtained from KKS activities. The effect of Karshiaka Karma Sena participation on employment and income has been worked out using a regression adjustment model. The results infer that participation in the KKS has enabled the labourers to increase their annually employed days by 24.74 days and to increase their average annual household income by Rs.. 65117. Overall, such innovative institutional intervention has opened up avenues for the sustenance of the livelihood security of agricultural labourers in the state.